CHALLENGES IN DEALING WITH THIRD AGE LONELINESS - Schneid, Ofer (E-Journal VFU, 2025)
Loneliness among adults is a broad and complex issue that receives increasing attention in recent years. As societies mature and demographic changes occur, the prevalence of loneliness among the elderly has become a significant public health concern. Despite its prevalence and impact on general well-being, treating loneliness among adults poses many challenges to caregivers, health professionals, and policy makers alike. Interventions range from social engagement programs to technological solutions designed to connect older adults. However, these interventions often encounter significant challenges and barriers, both existential and psychological in nature.